Numerical investigation on the effect of fire compartment opening width and heat release rate on the horizontal projection of smoke plume in a full-scale atrium - Mutafi M.A.; Nasif M.S.; Pao W.; Ismail F.B. (American Institute of Physics Inc., 2023)
Atrium is a modern architectural design of buildings that has an open space at the middle and contains multiple floors. In case of a fire in an atrium, the movement of the smoke plume is influenced by several factors. A CFD simulation using fire dynamic simulator (FDS6) software is conducted to investigate the effect of fire compartment opening width and heat release rate on horizontal Projections of smoke plume in a full scale atrium with down stand depths of 1m and 0.75m. It was found that, when the fire compartment opening width is small the smoke plume tends to flow away from the atrium structure. However, when the heat release rate is small the smoke plume flows closer to the atrium structure. 2018 Author(s).